(untitled) (Research, Society and Development, 2024)
The objective of this research was to analyze the indicators of violent crime in the state of Pará by surveying the Intentional Lethal Violent Crimes (ILVC) that occurred between 2018 and 2022. The research is quantitative, exploratory, and descriptive. The database analyzed is from the Adjunct Secretariat for Intelligence and Criminal Analysis and consists of the following variables: homicide, robbery resulting in death, and bodily injury resulting in death. The results showed that, out of a total of 14,116 crimes recorded during the period, homicide was the most frequent offense, with a rate of 94.40%, followed by robbery resulting in death (4.53%) and bodily injury resulting in death (1.07%). Observing the rates of Intentional Lethal Violent Crimes in comparison with the percentage of cases relative to the previous year, over the study period, for homicide and robbery resulting in death, there was an average annual decrease of -10.24% and -15.10%, respectively. In contrast, the number of crimes involving bodily injury resulting in death saw an annual increase of 5.68%. It is concluded that the reduction in violent crime indicators in the state of Pará during the period from 2018 to 2022 directly reflected the preservation of thousands of lives in the region due to the reduction of lethal violent deaths and provided a greater sense of security.